Liver Resection in a Patient with Absent Portal Vein Bifurcation: A Case Report - Minagawa, Noritake; Hachiya, Yasutaka; Nakashima, Hiroshi; Sako, Tatsuhiko; Tamura, Toshihisa; Ishikawa, Nami; Fukuyama, Tokihiko; Hirano, Yutaka; Hamada, Tetsuo (The Japanese Journal of Gastroenterological Surgery, 2012)
Absence of the portal bifurcation is an extremely rare anomaly and ligation of the portal vein without recognition of this anomaly would lead to tragedy. A 62-year-old man was followed up for 5 years for hepatitis type C. Computer tomography (CT) detected hepatocellular carcinoma, 6 cm in diameter, in segment 5 of the liver. CT and portography revealed absent portal vein bifurcation. Originating from the right dorsal branch, the portal vein, resembling the right paramedian vein, extended up to the cranial side, divided into sent several branches in the right lobe. It turned to the left side within the parenchyma, sending medial segmental portal branches and reached the umbilical fissure. Angiography also showed absence of the proper hepatic artery. The biliary distribution had no anomaly. We performed a right anterior subsegmentectomy safely with the preoperative transcatheter arterial chemoembolization and intraoperative injection of indocyanine green from the anterior inferior branch of the portal vein.